On extension of Donsker–Prokhorov invariance principle - Zemlys, Vaidotas (Lietuvos matematikos rinkinys, 2007)
The extension of Donsker–Prokhorov invariance principle for two-dimensional parameter summation process in Hölder space is provided for the case of independent non-identically distributed random variables.